El hombre eterno - Chesterton, G. K. (Gilbert Keith), 1874-1936; Chesterton, G. K. (Gilbert Keith), 1874-1936. (Madrid : Editorial Verbum, 2018)
Explores how the fulfillment of all of man's desires takes place in the person of Christ and in Christ's Church.
Online resource; title from PDF title page (Digitalia, viewed April 6, 2021)
Keywords: Catholic Church -- Apologetic works; Christianity and other religions; Apologetic writings; Electronic books